Artificial intelligence (AI) for home support interventions in dementia: a scoping review protocol. Issue 9 (21st September 2022) - Qi, Jinghan; Wu, Chuntao; Yang, Longfei; Ni, Cuiping; Liu, Yu
Abstract : Introduction: Dementia has become one of the significant causes of disability and dependency among older people globally. The proportion of people with dementia who are cared for at home has soared. The rapid growth of technology and data has stimulated artificial intelligence (AI) in patients with dementia at home. However, there are still tremendous opportunities and challenges in applying AI to patients with dementia at home, and there is no systematic overview. Methods and analysis: The review will adopt the Unified Theory of Acceptance and Use of Technology. This scoping review will follow the Joanna Briggs Institute scoping review methodology. The structure and content of this protocol follow the Preferred Reporting Items for Systematic reviews and Meta-analyses extension for Scoping Reviews checklist. The proposed study will consider applying AI technology for dementia patients living at home and their families. Authors will conduct systematic searches: China National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database, China Biology Medicine disc, PubMed, CINAHL, Web of Science Cochrane database, EBSCO, Ovid, PsycINFO, Embase. The extracted data will be processed qualitatively and described through tables. The findings are integrated by a narrative synthesis. This review aims to evaluate the nature and extent of the application of AI technology in patients with dementia at home through a systematic search of the literature. Ethics and dissemination: Scoping review is an analysis of existing data and therefore does not require ethical approval. We will publish our findings in a peer-reviewed journal. Scoping review protocol registration . DOI:10.17605/OSF.IO/3NU9C.